2006
DOI: 10.1016/j.ympev.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Historical population dynamics and demography of the eastern Atlantic pomacentrid Chromis limbata (Valenciennes, 1833)

Abstract: Recent studies have focused on the relationship between the marine fauna of the eastern Atlantic and the Mediterranean Sea, but within the Atlantic, little is known about genetic relationships between populations of the Macaronesian islands. In this study, we tested whether the paleo-climatology and paleo-oceanography of the region could predict the genetic relationships among three eastern Atlantic populations (Azores, Madeira, and Canaries) of a damselWsh, Chromis limbata, and compared our results with its M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…In agreement with this climatic history, the majority of the studies found evidence of Pleistocene bottlenecks that were likely caused by periods of strong ocean cooling (e.g. Consuegra et al 2002;Domingues et al 2006Domingues et al , 2007bDomingues et al , 2008Mäkinen and Merilä 2008). However, populations of diVerent species vary in their phylogeographic patterns and we are still far from a comprehensive picture of the evolution of the western European marine icthyofauna during the Pleistocene.…”
Section: Introductionmentioning
confidence: 67%
“…In agreement with this climatic history, the majority of the studies found evidence of Pleistocene bottlenecks that were likely caused by periods of strong ocean cooling (e.g. Consuegra et al 2002;Domingues et al 2006Domingues et al , 2007bDomingues et al , 2008Mäkinen and Merilä 2008). However, populations of diVerent species vary in their phylogeographic patterns and we are still far from a comprehensive picture of the evolution of the western European marine icthyofauna during the Pleistocene.…”
Section: Introductionmentioning
confidence: 67%
“…While most studies have supported the southern refugia hypothesis for the Mediterranean, Iberian Peninsula and Macaronesian islands (e.g. Chevolot et al, 2006;Domingues et al, 2006Domingues et al, , 2007aDomingues et al, , b, 2008, others have shown that some populations may have persisted in northern periglacial (1981) refugia (e.g. Provan et al, 2005;Hoarau et al, 2007).…”
Section: Diversity Patterns Of the Northeast Atlantic And Mediterranementioning
confidence: 99%
“…In West Africa, Madeira and part of the Canaries, as well as in pockets within the Mediterranean, warmer waters persisted, which caused vicariant speciation of many species pairs, with one member in West African Macaronesia and the other in the Mediterranean (e.g. Domingues et al, 2006). It is likely that A. hepsetus is a Mediterranean derivative of a mainly Atlantic stock, an interpretation favoured by the much higher genetic diversity of A. presbyter when compared with A. hepsetus.…”
Section: Biogeographical Implicationsmentioning
confidence: 99%